Technology-driven energy revolution: the impact of digital technology on energy efficiency and its mechanism - Wu, Hui; Han, Mengyu; Shen, Yang (Frontiers in Energy Research, 2023)
Introduction: Improving energy efficiency is significant for achieving carbon emission reduction and promoting the transformation of green economic development. In the sustainable development framework set out in the 2030 Agenda for Sustainable Development, Goal 7.3 explicitly aims to double the global rate of energy efficiency improvement by 2030. The rapid development of digital technology, along with its universality and penetrative characteristics, has provide a feasible solution for improving energy efficiency and environmental conditions. However, the theoretical understanding of the impact and underlying logic of digital technology on energy efficiency remains unclear. Methods: Based on the panel data of 30 provinces in China from 2006 to 2021, this paper adopts econometric methods, including two-way fixed effect, instrumental variable method, and Driscoll-Kraay standard error. It investigates the influence of digital technology on energy efficiency and its internal mechanism from single factor and all factor levels. Result: The results show that Digital technology, represented by industrial robots, significantly improves energy efficiency, whether measured by the energy consumption intensity of GDP or the total-factor energy efficiency estimated using the SBM-GML model. The results still hold even after conducting endogeneity tests and robustness tests. Digital technology can improve energy efficiency by increasing virtual industrial agglomeration and promoting outward foreign direct investment. Discussion: In addition to promoting the theoretical understanding of the impact of digital technology on energy efficiency and exploring its mechanism, this paper also provides empirical evidence for policy makers and enterprises to formulate effective measures and strategies to improve energy efficiency under the background of digital economy.